Attending to the Big Picture: Mood and Global Versus Local Processing of Visual Information - Gasper, Karen; Clore, Gerald L. (Psychological Science, 2002)
Two experiments employed image-based tasks to test the hypothesis that happier moods promote a greater focus on the forest and sadder moods a greater focus on the trees. The hypothesis was based on the idea that in task situations, affective cues may be experienced as task-relevant information, which then influences global versus local attention. Using a serial-reproduction paradigm, Experiment 1 showed that individuals in sad moods were less likely than those in happier moods to use an accessible global concept to guide attempts to reproduce a drawing from memory. Experiment 2 investigated the same hypothesis by assessing the use of global and local attributes to classify geometricfigures. As predicted, individuals in sad moods were less likely than those in happier moods to classify figures on the basis of globalfeatures.